Correlation between Duration of Antiretroviral Therapy and Glomerular Filtration Rate in People Living with HIV/AIDS: A Cross-sectional Study in Cirebon, West Java, Indonesia - Ayudhipasha, Tiara Sekar; Herdwiyanti, Menik; Sedayu, Sedayu (GHMJ (Global Health Management Journal), 2025)
Background: West Java ranks the highest Province with Human Immunodeficiency Virus (HIV) case in 2023. An estimated 1.648 patients estimated receive antiretroviral therapy (ART). Kidney disease contributes mortality amongst people living with HIV/AIDS (PLWH). Tenofovir disoproxil fumarate (TDF)-based ART was associated as risk factor of kidney disorders, indicate by declining glomerular filtration rate (GFR). However, there is limited study whether kidney disease among PLWH were related to ART use in Indonesia. Aims: To determine correlation between duration of antiretroviral therapy and glomerular filtration rate (GFR) in people living with HIV/AIDS. Methods: This is an observational study with cross-sectional design. Eighty-nine HIV patients on antiretroviral therapy for at least three months with normal baseline GFR were studied. Estimated GFR calculated using the Cockcroft-Gault equation. Data obtained were analyzed with spearman correlation test. Results: Among 89 subjects, as many as 38 patients (42.7%) on therapy less than 12 months, 29 patients (32.6%) were on ART more than 24 months, and 22 patients (24.7%) 12-24 months. ART with normal kidney function were 62 patients (69.7%). Whereas 29.2% were mildly decrease GFR, and only 1.1% were mild to moderate decrease GFR. The analytical statistic showed a no significant between duration of antiretroviral therapy and GFR in PLWH with a p-value of 0.199 and Spearman’s r of 0.137. Conclusion: There was no significant correlation between duration of antiretroviral therapy and glomerular filtration rate in PLWH.